Significance Of Differences From Sumatera, Kalimantan, and Sulawesi Coal Based On Cluster Analysis And Statistics - Rachman, Rizki Satria; Hidayat, Rahmat; Rahmat, Soleh Basuki; Wibisono, Sigit Arso (Journal of Applied Geology, 2024)
Indonesia has a complex geological structure with coal potential dominated by 3 main islands, Sumatra (SMS), Kalimantan (KS), and Sulawesi (SLS). However, the characteristics of coal on these three islands are not explained further. Therefore, this research is intended to see the significant differences in coal on Sumatra, Kalimantan and Sulawesi in terms of their characteristics. The research methods carried out include literature study, field activities, laboratory analysis including proximate analysis (total moisture, moisture, volatile matter, fixed carbon), total sulfur, calories, specific gravity, HGI, ultimate analysis (C, H, N, O, S), and coal ash analysis, as well as data processing using cluster analysis and principle component analysis (PCA). Result, 55 coal samples were obtained on these three islands which were divided into 9 main clusters with 50% similarity. Kalimantan Island has coal with an increase in TiO2, Al2O3, Na2O oxides with carbon and nitrogen elements. Sumatra Island has coal with increased TM, M, MnO, CaO, MgO, Fe2O3, and SO3 and a slight influence of HGI, TS. Meanwhile, Sulawesi Island has coal with complex parameters and an increase in calorific value. It is interpreted that the differences in coal characteristics are influenced by the different geological settings of these three islands in the past until resen.